The commitment of dentists to prescribe antibiotics in modern conditions - Svetlana Tuleutayeva; Sholpan Kaliyeva; Kanagat Mukhtarova; Kulzhahan Shauyenova; Darkhan Tuleutayev; Gulden Salkenova; Aisulu Zhumadilova (Elsevier, 2021)
Aim or Purpose: The aim of this research was to study different patterns of antibacterial drugs prescribing in dentistry practice in Central Asian region. Materials and Methods: The online survey of 108 dentists was conducted. The online questionnaire included 18 questions. Results: Almost half of respondents (42,1%) frequently prescribed antibiotics. The most preferred antibiotics were from the group of penicillin (46.6% of cases). The following groups of antibiotics also were prescribed by dentists: fluoroquinolones (42.6%), nitroimidazoles (30.7%), cephalosporins 3 generations (18.8%) and lincozamines (16.8%). The duration of therapy in was 5-7 days in 62.3%, the rest of patients took antibiotics 3-5 days. The 67.7% of respondents prescribed monotherapy. The most common combination of antibiotic drugs were ciprofloxacin and metronidazole (26%). The indications for ambulatory antibiotic prescription were tooth extraction (48.1%) and apical periodontitis (38.7%). Most of the respondents (61.3%) answered that they are familiar with the principles of rational antibiotic therapy. The 84% of respondents prescribe an antibiotic with an average therapeutic dose. The replacement of antibiotic because of inefficiency was provided in 84.5%. In the absence of an allergic history 48.1% of dentists prescribe ciprofloxacin. Conclusions: Thus, in the course of the study, it was found that the majority (64%) of antibiotic appointment were irrational in outpatient dental practice. The most common observation was prescribing antibiotics and their combinations without direct indications. This trend is a cause for concern and requires additional measures aimed at increasing awareness of dentists about antibiotic treatment as well as standardization of prescription.